Flora and vegetation of Sierra de Órganos, Sombrerete, Zacatecas, Mexico - Enríquez Enríquez, E. David; Koch, Stephen D.; González-Elizondo, M. Socorro (Instituto de Ecología, A.C., 2003)
The Sierra de Organos, located in the western part of the state of Zacatecas, Mexico, is a mountainous area consisting principally of rhyolitic pinnacles. The area was declared a National Park in November 2000. The collection and identification of the vascular flora of the area resulted in a floristic list that includes 406 species, 254 genera, and 75 families. The most diverse families are Asteraceae, Poaceae and Fabaceae. On the basis of physiognomy and dominant species we recognize nine vegetation types, which were delimited and mapped with the aid of aerial photographs, botanical collections, and 29 sample plots. The vegetation types include Quercus woods, Pinus woods, mixed Pinus and Quercus woods, mixed Pinus and Juniperus woods, vegetation of rocky streams, vegetation of rock pinnacles, Mimosa and Opuntia scrub, grassland, and aquatic-subaquatic vegetation.